Method for Determining the Maximum Density and Optimal Moisture Content of Coarse-Grained Soils by the Proctor Method (Eurasian Research Bulletin, 2023)
This article presents the results of a study to determine the maximum density and optimal moisture content of coarse-grained soils with sandy aggregates using a large-size Proctor test equipment. Recommended values of maximum density and optimal moisture content depend on the size of the fraction